Multivariate assessment of barriers materials for treatment of complex groundwater rich in dissolved organic matter and organic and inorganic contaminants. Issue 4 (August 2017) - Kozyatnyk, Ivan; Lövgren, Lars; Tysklind, Mats; Haglund, Peter
Highlights: Material for treatment DOM rich groundwater from heavy metal and organic pollutants. Removal efficiency was analyzed with coefficients of adsorption isotherms. Activated carbon, peat, fly ash were the most effective for organics removal. Fly ash was the best for simultaneous removal of metal and organic pollutants. Batch adsorption and PCA are effective for selecting materials for water treatment. Abstract: This study focused on the challenges of treating groundwater rich in dissolved organic matter and contains both heavy metals and organic pollutants. Activated carbon, fly ash, lignite, peat, torrefied organic material and zero-valent iron were tested as prospective materials for permeable barriers. Removal of different pollutants was analyzed using coefficients of the Freundlich equation for adsorption isotherms. Principal components analysis was used to visualize similarities and differences in pollutant removal efficiency and sorbent capacity between barrier materials. Fly ash, iron (aerobic conditions) and activated carbon were found to be promising materials for dissolved organic matter removal. Fly ash was the most effective material for metal removal, and fly ash, activated carbon and peat were the most effective materials for removal of organic contaminants. Thus, fly ash shows the most potential for simultaneous removal of metals and organic pollutants. However, it has limited capacity for removing neutral halogenated aromatic compounds. For these, zero-valent iron (aerobic conditions) has greater capacity, probably because of the formation of a porous layer of iron oxyhydroxide. In summary, batch adsorption experiments followed by principal components analysis evaluation of the results are useful tools for selecting suitable materials for treatment of groundwater contaminated with multiple organic and inorganic pollutants.